Financial Development and Energy Use (Consumption), Urbanization and Industrialization Role in South Africa - Simon, Angela Uzoamaka (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This paper looks at the relationship between energy consumption, financial development, economic growth, the role of industrialization and urbanization in South Africa from the year 1970 to 2014. The study employs the Johansen co-integration test and Vector Error Correction model (VECM) also, Granger causality test is used for the study. The result confirms that there is a long-run relationship between the variables (energy consumption, financial development, economic growth, industrialization and urbanization) in South Africa. More so, urbanization, financial development and industrialization are positively correlated to energy consumption in the long-run. The result obtained shows the long-run bidirectional causality between industrialization and energy utilization, financial development and energy consumption and also financial development and industrialization. Therefore the study recommends a well-developed financial system, an effective policy towards increasing the effectiveness of economic activities of the country. Likewise, promoting urbanization and industrialization helps in development processes. Hence increases energy consumption. Keywords: Energy Consumption, Financial development, Economic growth, South Africa, Time series, Co-integration, Vector error correction model (VECM).

ÖZ : Bu bildiri aynı zamanda enerji tüketimi, finansal gelişme, ekonomik büyüme, 2014 çalışma Johansen eş-bütünleşme testi ve Vektör Hata Düzeltme modeli (VECM) istihdam için 1970 yılında Güney Afrika'da sanayileşme ve kentleşmenin rolü arasındaki ilişki bakar Granger nedensellik testi çalışması için kullanılır. Sonuç Güney Afrika değişkenlerin (enerji tüketimi, finansal gelişme, ekonomik büyüme, sanayileşme ve kentleşme) arasında uzun dönemli bir ilişki olduğunu doğrulamaktadır. Daha çok, kentleşme, finansal gelişme ve sanayileşme pozitif uzun vadede enerji tüketimi ile ilişkilidir. Elde edilen sonuç sanayileşme ve enerji kullanımında, finansal gelişme ve enerji tüketimi ve aynı zamanda mali gelişme ve sanayileşme arasındaki uzun dönemli çift yönlü nedenselliği göstermektedir. Bu nedenle çalışma iyi gelişmiş finans sistemini, ülkenin ekonomik faaliyetlerinin etkinliğini artırmaya yönelik etkili bir politika önermektedir. Aynı şekilde, kentleşme ve sanayileşme teşvik geliştirme süreçlerinde yardımcı olur. Bu nedenle, enerji tüketimini artırır. Anahtar Kelimeler: Enerji Tüketimi, Finansal gelişme, ekonomik büyüme, Güney Afrika, Zaman serisi, Eş-bütünleşme, Vektör Hata Düzeltme Modeli (VECM).
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2016. Supervisor: Assoc. Prof. Dr. Hasan Güngör.
Keywords: South Africa - Economic Growth; Economic Conditions and Development - South Africa; Energy Consumption; Financial development; Economic growth; South Africa; Time series; Co-integration; Vector error correction model (VECM); Economics